2021
DOI: 10.1101/2021.11.15.468744
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zika virus-induced TNF-α signaling dysregulates expression of neurologic genes associated with psychiatric disorders

Abstract: Zika virus (ZIKV) is an emerging flavivirus of global concern. ZIKV infection of the central nervous system has been linked to a variety of clinical syndromes, including microcephaly in fetuses and rare but serious neurologic disease in adults. However, the potential for ZIKV to influence brain physiology and host behavior following recovery from apparently mild or subclinical infection is less well understood. Furthermore, though deficits in cognitive function are well-documented following recovery from neuro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 119 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Total RNA from harvested tissues was extracted using Zymo Direct-zol RNA Miniprep kit, as per manufacturer instructions (Zymo, #R2051). Total RNA extraction from cultured cells, cDNA synthesis, and subsequent qRT-PCR were performed as previously described (22, 53). Cycle threshold (CT) values for analyzed genes were normalized to CT values of the housekeeping gene 18 S (CT Target – CT 18S = ΔCT).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA from harvested tissues was extracted using Zymo Direct-zol RNA Miniprep kit, as per manufacturer instructions (Zymo, #R2051). Total RNA extraction from cultured cells, cDNA synthesis, and subsequent qRT-PCR were performed as previously described (22, 53). Cycle threshold (CT) values for analyzed genes were normalized to CT values of the housekeeping gene 18 S (CT Target – CT 18S = ΔCT).…”
Section: Methodsmentioning
confidence: 99%
“…A role for Zika virus-induced TNFa-signaling in the induction of psychiatric disorders has been recently reported [47]. In this case, authors suggested that ZIKVinfected neurons would be the main source of TNFa expression.…”
Section: Discussionmentioning
confidence: 82%